2000
DOI: 10.1103/physrevb.61.10223
|View full text |Cite
|
Sign up to set email alerts
|

Determination of InP(001) surface reconstructions by STM and infrared spectroscopy of adsorbed hydrogen

Abstract: The atomic structure of the InP͑001͒ reconstructions has been identified by scanning tunneling microscopy and infrared spectroscopy of adsorbed hydrogen. The four phases, in order of decreasing phosphorous coverage, are c(2ϫ2)/p(2ϫ2), P ϭ2.0 ML; (2ϫ1), P ϭ1.0 ML; (2ϫ4), P ϭ0.25 ML, and ␦(2ϫ4), P ϭ0.125 ML. The (2ϫ2) consists of phosphorous dimers adsorbed onto a layer of P atoms. Removal of the P adatoms at 300°C, produces the (2ϫ1), which is terminated with a complete layer of buckled phosphorous dimers. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…In all experimental conditions the surface presents a (2x4) reconstruction except for the lower temperature values, enclosed by dashed lines in figure 1, where RHEED showed a (2x1) pattern. The experimental conditions sampled in this work correspond, according to recent results [13][14][15], to the different phases of the (2x4) InP(001) reconstructed surface, which remains stable although ranging from anion-rich to cation-rich stabilized stoichiometry. Since (2x4) InP(001) surface reconstruction can exist in different surface phases [13][14][15], the RD signal is not expected to be a linear function of In dimers existing in the surface, but a more complicated function that depends on the detailed surface structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all experimental conditions the surface presents a (2x4) reconstruction except for the lower temperature values, enclosed by dashed lines in figure 1, where RHEED showed a (2x1) pattern. The experimental conditions sampled in this work correspond, according to recent results [13][14][15], to the different phases of the (2x4) InP(001) reconstructed surface, which remains stable although ranging from anion-rich to cation-rich stabilized stoichiometry. Since (2x4) InP(001) surface reconstruction can exist in different surface phases [13][14][15], the RD signal is not expected to be a linear function of In dimers existing in the surface, but a more complicated function that depends on the detailed surface structure.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental conditions sampled in this work correspond, according to recent results [13][14][15], to the different phases of the (2x4) InP(001) reconstructed surface, which remains stable although ranging from anion-rich to cation-rich stabilized stoichiometry. Since (2x4) InP(001) surface reconstruction can exist in different surface phases [13][14][15], the RD signal is not expected to be a linear function of In dimers existing in the surface, but a more complicated function that depends on the detailed surface structure. However, based on the RDS spectra calculated by N. Esser et al [14] for the different phases in the (2x4) reconstruction for InP(001), we have estimated the levels of RD signal corresponding to each phase.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of surface reconstruction for the dilute coverage limit (θ=0.1) was motivated by the observation that the two most common reconstructions of InP(001) and GaP(001) under ambient conditions are the M -rich mixed-dimer δ(2 × 4) and the P-rich (2 × 1), depending on the specific growth environment [35][36][37][38][39][40][41][42][43] . Of these, experiments on InP(001) have shown that the P-rich surface features stable P-P dimers that exhibit weak oxygen uptake at ambient temperature, whereas the M -rich mixed-dimer δ(2×4) surface reacts readily with oxygen 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Energies are given with respect to two reference configurations. The first is with respect to InP(001) δ(2 × 4)-the most commonly observed In-rich reconstruction in vacuum 16,17 -and molecular O 2 . The second is with respect to InP(001) δ(2 × 4), H 2 O, and H 2 .…”
Section: Oxides Of Indium Phosphide (001)mentioning
confidence: 99%
“…In-plane axes were aligned along the [110] and [111] crystallographic directions. A total of 142 water molecules were inserted between periodic slab images, filling an intermediate region about 16.5Å wide (the density was chosen to match the experimental density of liquid water). To generate the initial configuration for the interface, we first ran classical simulations for bulk water using the TIP4P potential.…”
mentioning
confidence: 99%